Family Victimization Among Canadian Sexual and Gender Minority Adolescents and Emerging Adults - Blais, Martin; Coutu, Cameron; Boislard, Marie-Aude; Hart, Trevor A.; Walker, Mattie; Parent, Sylvie (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: This paper examines family victimization, well-being, and resilience among sexual and gender minority (SGM) adolescents and emerging adults aged 15 to 29 years. Methods: Self-reported data were collected online (2019-2020) from 1,971 Canadian SGM youths. We used logistic regression to estimate the odds of: (a) having experienced family victimization over the past 12 months; (b) reporting well-being across the various frequencies of family victimization; and (c) thriving (i.e., flourishing despite having experienced family victimization). Results: About 36% of participants experienced family victimization within the previous 12 months, with 13% reporting recurrent family victimization. Recurrent victimization was more prevalent among trans and nonbinary youths as compared to cisgender men, and was also more prevalent among socioeconomically disadvantaged participants. Recurrent victimization was significantly associated with higher odds of reporting internalized heterosexism, efforts to conceal gender and sexual orientation, languishing mental health, social anxiety, loneliness, and post-traumatic stress symptoms. Thriving participants were less likely to experience activity restrictions or to live with at least one parent, and more likely to score higher on authenticity scales, to report proactive norms against violence within their family, and to have food and economic security. Conclusion: Despite recent advances in SGM rights and acceptance, SGM youths still face family victimization and compromised well-being. Implications: These findings underline the importance of screening for family violence among SGM youths, particularly among trans youths and those of lower socioeconomic status. Findings also underline the importance of providing SGM youth both a safe family environment and material security.